Capital markets' reactions to social information announcements. (10th September 2008) - Parsa, Sepideh; Deng, Leo Xiaobing
This paper aims to investigate whether the London Stock Exchange (LSE) reacts to social information announcements by new entrants to LSE over a period of five years. Out of a total of 249 non-financial companies that joined LSE, only 66 social information items were announced by 40 companies. For each individual information item, the corresponding company's share price movements are observed and compared with the market benchmark. Having measured abnormal returns for all the price movements, it transpires that on the day of announcement 71% of the reported social information items corresponded with positive abnormal returns. Even though our findings illustrate an overall positive market response to the announcement of social information, the observation of some negative reactions indicates that the release of social information by companies may not always meet its intended target and enhance corporate reputation as perceived by investors.